Attitudes of professionals towards incest clients in the Northern Province of South Africa - Setwaba, M. B. (University of Limpopo, 2000)
Refer to the document
Thesis ((M. A. (Clinical Psychology)) --University of the North, 2000
Keywords: Incest clients; Incest -- South Africa -- Limpopo; Sex crimes -- South Africa -- Limpopo; Incest victims -- South Africa -- Limpopo; Clinical psychology